Kecerdasan Budaya dan Gaya Belajar Mahasiswa yang Merantau di DKI Jakarta - Arif Triman; Abdillah Abdillah (Lembaga Penelitian Universitas YARSI, 2017)
Indonesia is a developing country with an uneven educational infrastructure development. It impacts the number of students from rural areas to big cities to get a decent education. Many of those students are experiencing difficulties when entering a new culture, thus disrupting their adjustment, especially in learning styles. The purpose of this study is to investigate any possible correlation between cultural intelligence and Grasha learning style. Participants in this study were 121 students in DKI Jakarta. Cultural Intelligence Scale and Grasha-Riecment Learning Scale Style were used as instruments in this study. Using regression analysis, it was found that 2 of 6 learning style (Collaborative learning style and Independent learning style) were found to have significant role in Cultural Intelligents.